Working conditions that contribute to absenteeism among nurses in a provincial hospital in the Limpopo Province - Nyathi, M; Jooste, K (Curationis (Pretoria), 2008)
Absenteeism results in an increased workload for nurses who stand in for colleagues and can lead to situations in which a lack of motivation among nurses and a lowering of the quality of patient care may occur. The researcher observed that certain conditions, such as inflexible working schedules, were given as reasons for the absenteeism in units in a provincial hospital. A non-experimental, descriptive, quantitative study was undertaken. The purpose of the article was to describe the working conditions that contribute to absenteeism among the professional and sub-professional nurses at a provincial hospital in the Limpopo province of South Africa. The sample included 107 professional nurses and 163 sub-professional nurses who voluntarily agreed to participate in the study. A questionnaire was used to collect data, which was analysed by using descriptive and inferential statistics. The findings of this study indicated that personal and managerial characteristics, and organisational and working conditions may lead to absenteeism in the workplace. This article focuses on the working conditions that are constraints, namely inadequate group cohesion, inadequate delegation of autonomy, role ambiguity, ineffective routinisation and the effect of the workload in the workplace. Recommendations are made for improving working conditions to combat absenteeism among nurses. The limitations of this study are highlighted.